Transition in Infant and Young Child Feeding Practices in India - Puri, Seema (Current Diabetes Reviews, 2017)
Introduction: Optimal infant and young child feeding, which includes initiation of breastfeeding within one hour of birth, exclusive breastfeeding for first six months, age appropriate complementary feeding after six months along with continued breastfeeding for 2 years and beyond, is a public health intervention to prevent child morbidity, mortality and malnutrition [1]. In India, even though institutional delivery rates are increasing, only 44% women are able to breastfeed their babies within one hour of delivery. While 65% children are exclusively breast fed for the first six months, the median duration of breastfeeding is 24.4 months and complementary feeding rates are 50%. To achieve optimal IYCF practices, each woman should have access to a community based IYCF counseling support system. Efforts are therefore needed to upgrade skill based training of health workers and revive and update the Baby Friendly Hospital Initiative (BFHI). To promote and sustain breastfeeding amongst working women, it is essential to ensure adequate maternity leave, crèches at work place, flexible working hours, and provision of physical space for breast feeding at work place. It is imperative to also create public awareness about the dangers of bottle and formula feeding and to provide accurate information on the appropriate complementary food to be given to infants. Conclusion: In conclusion, India needs to make serious efforts to overcome malnutrition with not only prioritized IYCF policies but also their effective implementation in place.
Keywords: complementary feeding